Company Value in the 2018-2021 Period in Manufacturing Companies: Influencing Variable Factors - Hidayat, Imam; Aprilia Sari, Petty; Suhariyanto; Sukiranto (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To determine the effect of liquidity and solvency on company value with profitability as an intervening variable. Background Problem: In maintaining the continuity of the business and to increase the value of the company which is a reflection of public trust in a company for the results that have been achieved after going through the activity process for several years. Novelty: Conducting research with different data and different sectors on company value with profitability as an intervening variable. Research Method: There were 28 companies sampled in this research which were taken based on purposive sampling. These variables can be seen from the company's financial reports published on the Indonesia Stock Exchange for 4 years, namely from 2018 to 2021 and processed and analyzed using SPSS 23 software. Findings/Results: That partially liquidity has a significant positive effect on profitability, solvency has an effect insignificant negative effect on profitability, liquidity and solvency have an insignificant negative effect on company value, profitability has a positive effect on company value, partial profitability is able to mediate liquidity on company value. Conclusion: In consumer sector companies, when making investments, it is best to pay attention to the company value or financial reports as considerations when making decisions